EDUKASI PENCEGAHAN DAN DETEKSI DINI RISIKO OBESITAS SENTRAL MENGGUNAKAN PARAMETER RASIO LINGKAR PINGGANG DAN PANGGUL PADA REMAJA SEKOLAH MENENGAH ATAS - Ma’arif, Mohammad Zainul; Renowening, Yuniars; Mahmudah, Himmatunnisak; Dwi Noviati, Titik; Ridha, Alfan (Gapenas Publisher, 2024)
Obesity is characterized by excessive or abnormal fat accumulation, and poses significant health risks. Obesity, especially central obesity, increases the risk of various chronic diseases such as type 2 diabetes, heart disease, hypertension, metabolic disorders and stroke. Therefore, it is important to make efforts to prevent and early detect the risk of central obesity in adolescents to prevent an increase in degenerative diseases in the future. This activity is divided into two forms of activity, namely an educational workshop on the prevention of central obesity, and anthropometric measurements for early detection of central obesity. Anthropometric measurements carried out include measurements of body weight, height, hip circumference and pelvic circumference. This activity was carried out at Sugeng Hartono University with the target being students from Polokarto High School, Sukoharjo. A total of 39 participants, 4 people (10.3%) were overweight, 1 person was stage 1 obese (2.6%), and 1 person was stage 2 obese (2.6%). Measurement of the waist-to-hip circumference ratio showed that 37 people (94.9%) were not at risk of central obesity, and 2 people (5.1%) were at risk of central obesity. Education and anthropometric measurements provide important insight into obesity status and health implications in adolescents to prevent degenerative diseases in the future